2021
DOI: 10.3389/fcell.2021.709408
|View full text |Cite
|
Sign up to set email alerts
|

Although Anatomically Micrometers Apart: Human Periodontal Ligament Cells Are Slightly More Active in Bone Remodeling Than Alveolar Bone Derived Cells

Abstract: The periodontal ligament (PDL) and the alveolar bone are part of the periodontium, a complex structure that supports the teeth. The alveolar bone is continuously remodeled and is greatly affected by several complex oral events, like tooth extraction, orthodontic movement, and periodontitis. Until now, the role of PDL cells in terms of osteogenesis and osteoclastogenesis has been widely studied, whereas surprisingly little is known about the bone remodeling capacity of alveolar bone. Therefore, the purpose of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…Figure 1A ). As in previous studies from our group ( Karlis et al, 2020 ; Loo-Kirana et al, 2021 ), the observed Alizarin Red staining was due to so-called nodules or hot-spots of mineralization that formed on top of the fibroblasts ( Figure 1D ). Interestingly, mineralization medium only induced osteopontin expression when compared to normal medium, whereas RUNX-2, Collagen-I expression and the activity of Alkaline phosphatase was not influenced, not by mineralization medium nor by metformin.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Figure 1A ). As in previous studies from our group ( Karlis et al, 2020 ; Loo-Kirana et al, 2021 ), the observed Alizarin Red staining was due to so-called nodules or hot-spots of mineralization that formed on top of the fibroblasts ( Figure 1D ). Interestingly, mineralization medium only induced osteopontin expression when compared to normal medium, whereas RUNX-2, Collagen-I expression and the activity of Alkaline phosphatase was not influenced, not by mineralization medium nor by metformin.…”
Section: Discussionsupporting
confidence: 82%
“…These promising results with metformin in animal studies as well as in clinical studies urge mechanistic insight using a relevant cell system. Periodontal ligament fibroblasts anchor teeth in bone and also play a crucial role in both osteogenesis and osteoclastogenesis, processes that can be elegantly mimicked in vitro (De Vries et al, 2017;Ruppeka-Rupeika et al, 2018;De Vries et al, 2019;Karlis et al, 2020;Loo-Kirana R.;Gilijamse M.;Hogervorst J., 2021). Support for the relevance of periodontal ligament fibroblasts comes from an animal study where periodontal ligament fibroblasts were shown to play a key role in alveolar bone regeneration (Ren et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the stromal compartment was collectively divided into Plap-1 + fibroblastic cells or Ibsp + osteo-/cementoblastic cells in a mutually exclusive manner. Plap-1 is also highly expressed in the human PDL and used as a cultured PDLC marker (Yamada et al 2001; Loo-Kirana et al 2021; Mun et al 2022). RNA velocity analysis indicated that cluster 9, Plap-1 high , with a positive velocity of Plap-1 mRNA, constituted a potential cellular source of other PDL clusters.…”
Section: Discussionmentioning
confidence: 99%
“…Plap-1 is also highly expressed in the human PDL and used as a cultured PDLC marker (Yamada et al 2001;Loo-Kirana et al 2021;Mun et al 2022). RNA velocity analysis indicated that cluster 9, Plap-1 high , with a positive velocity of Plap-1 mRNA, constituted a potential cellular source of other PDL clusters.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoclasts differentiate from monocyte–macrophage‐lineage progenitor cells by two critical cytokines, macrophage colony‐stimulating factor and receptor activator of nuclear factor‐κB (RANK) ligand (RANKL). PDLFs, osteoprogenitors, and osteoblasts express RANKL, which binds to the RANK receptor on osteoclast progenitor cells (Loo‐Kirana et al, 2021). RANKL‐RANK binding is followed by signal transduction via the NF‐κB/NFATc1 pathway, leading to osteoclast‐specific gene expression.…”
Section: Biological Backgrounds Of Tooth Transplantation and Replanta...mentioning
confidence: 99%